Unveiling the Power of Traditional Soodha Vallathi Urundai against Gastric Cancer Cells - M M.D, Revathi; G. M.D, Subash Chandran; K.S. M.D, Uma (Journal of Neonatal Surgery, 2025)
Introduction: Cancer-related deaths from gastric cancer (GC) are significant worldwide, and there is an urgent need for new, efficient therapies. Siddha medicine, known for its extensive historical use, presents potential anticancer compounds. Soodha Vallathi Urundai (SVU) is a time- honored remedy believed to have healing benefits; however, its effect on gastric cancer remains largely unexplored. This study aimed to assess the anticancer efficacy of SVU in a gastric cancer model (MKN-45P), focusing on tumor development, angiogenesis, blood parameters, and metabolic indicators. Methodology: Three groups of Balb/c mice (n=6) received injections of MKN-45P tumor cells and then administered SVU (200 mg/kg). Tumor advancement and blood were assessed, including biochemical tests, immunohistochemistry for CD31, LDH, and TNF-α, and white blood cell counts, were performed. Results: SVU treatment markedly inhibited tumor growth (tumor size in the SVU-treated group: 2.45 ± 0.63 cm versus 3.02 ± 0.73 cm in the MKN-45P group, p < 0.05). The phrase of CD31 in tumors was reduced in SVU-treated sector (0.32 ± 0.12) relative to the MKN-45P group (0.72 ± 0.21, p < 0.01). Haematological examination showed elevated WBC levels (14.1 ± 0.754 ×10³/µL in the SVU-treated group compared to 11.2 ± 1.58 ×10³/µL in the MKN-45P group, p < 0.05). LDH levels were considerably lower in SVU group (0.136 ± 0.024 IU/L compared to 0.226 ± 0.0115 IU/L in the MKN-45P group, p < 0.01). Conclusions: SVU showed notable anticancer effects, decreasing tumor size, angiogenesis, and metabolic indicators, while enhancing immune response with minimal toxicity. These findings indicate that SVU may be a viable treatment option for gastric cancer, necessitating additional research.